Applied ethics an introduction - Attfield, Robin (Polity Press, 2023)
"Philosophy has provided us with a wealth of moral and ethical theories. Applied ethics is the study of practical moral issues and our best philosophical theories, and how each can inform the other. Acclaimed philosopher and textbook author Robin Attfield invites students to reflect on the key problems of our time. Through lively case studies of topics related to health care, international development, the environment, abortion, punishment and more, he reveals how standard ethical theories can be tested on these real-life scenarios and, if necessary, revised or discarded. Students are encouraged to be their own philosophers, exploring and reaching coherent stances across a wide range of areas of everyday concern. Covering a typical applied ethics syllabus in a comprehensive and accessible manner, Applied Ethics will motivate philosophy students to engage with the most pressing moral issues of the twenty-first century" -- Amazon.